2013
DOI: 10.1111/php.12111
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐Dependent Photochemistry and Photophysics of “MiniSOG,” a Protein‐Encased Flavin

Abstract: Selected photochemical and photophysical parameters of flavin mononucleotide (FMN) have been examined under conditions in which FMN is (1) solvated in a buffered aqueous solution, and (2) encased in a protein likewise solvated in a buffered aqueous solution. The latter was achieved using the so-called "mini Singlet Oxygen Generator" (miniSOG), an FMN-containing flavoprotein engineered from Arabidopsis thaliana phototropin 2. Although FMN is a reasonably good singlet oxygen photosensitizer in bulk water (ϕΔ = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
150
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(168 citation statements)
references
References 57 publications
6
150
2
Order By: Relevance
“…Furthermore, independently of the 1 RB ⁄ into the protein play a role in the intra-protein photosensitization of 1 O 2 . Nevertheless, the present results suggest that RB encased in BSA is almost 10-and 100-times more efficient 1 O 2 generator than miniSOG [10,11] and GFP [8] proteins, respectively.…”
Section: Photosensitizing Properties Of Rb Bound To Bsacontrasting
confidence: 50%
See 1 more Smart Citation
“…Furthermore, independently of the 1 RB ⁄ into the protein play a role in the intra-protein photosensitization of 1 O 2 . Nevertheless, the present results suggest that RB encased in BSA is almost 10-and 100-times more efficient 1 O 2 generator than miniSOG [10,11] and GFP [8] proteins, respectively.…”
Section: Photosensitizing Properties Of Rb Bound To Bsacontrasting
confidence: 50%
“…However, later photophysical characterization studies of miniSOG demonstrated that the photosensitized efficiency of 1 O 2 is much lower, e.g. U D % 0.03, due to the role of the peptide backbone to enhance electron-transfer (Type I) in detriment of energy-transfer (Type II) mechanism [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…Additional applications for miniSOG include new methods for optical immunodetection [47], the development of new methodologies for imaging protein-protein interactions in intact cells [48 ] and chromophore-assisted light inactivation, a powerful technique where 1 O 2 photosensitization can be used to selectively interfere with the function of proteins in close proximity [49]. Detailed photochemical characterization indicates that miniSOG initiates other photoinduced electron transfer processes in addition to 1 O 2 production [50,51]. Further photosensitizer improvements could thus be obtained through protein engineering strategies.…”
Section: Singlet Oxygen Generationmentioning
confidence: 98%
“…For phiLOV2.1, which has been engineered towards higher photostability by several rounds of directed evolution, it has been proposed that the increased photostability is a result of a more rigid packing of the chromophore and especially its ribityl chain in the protein 10 . FMN itself has a high quantum yield for the generation of singlet oxygen and other reactive oxygen species under illumination 12,61,62 , which are likely to play a major role in irreversible photobleaching. In addition to brightness and photostability, we also compared the spectral characteristics of the LOV-based FPs.…”
Section: Articlementioning
confidence: 99%